Tofu Whey-Based Media for Probiotic Lactiplantibacillus plantarum D4 as a Halal Starter Culture - Maulidiyah, Hikmah; Mustafa, Irfan; Jatmiko, Yoga Dwi; Ibrahim, Salam A. (UIN Sunan Gunung Djati Bandung, 2024)
In recent years, the development of probiotic-based fermented products with halal status has been a concern. The use of growth medium has relied on de Man Rogosa and Sharpe (MRS) as a relatively expensive standard medium, and its halal status is still uncertain. Extensive research has been carried out to investigate the development of low-cost halal alternative media for the cultivation of probiotic lactic acid bacteria (LAB). This study aimed to develop a probiotic halal and low-cost culture medium using a tofu whey-based medium. This study used three tofu whey-based media - A (tofu whey 100%), B (tofu whey 94.5%, molasses 3%, skim milk 2.5%), C (tofu whey 92.5%, molasses 3%, cheese whey 2.5%, tomato extract 2%), and MRS broth as a standard medium. Bacterial populations, total sugars utilized, total lactic acids produced, low pH (2.0) tolerance, and high bile salt concentration (oxgall 1.5%) were assayed. The highest bacterial population after 48 h of incubation was shown by medium B compared to medium MRS (12.34 ± 0.87 and 11.48 ± 0.3 log CFU/mL). Total sugars utilized by 48.28 ± 2.89, 38.89 ± 6.94, 39.14 ± 4.24, and 76.00 ± 1.41 %; on the other hand, total lactic acids produced by 0.16 ± 0.12, 0.03 ± 0.04, 0.31 ± 0.03, and 2.25 ± 1.48 % in A, B, C, and MRS, respectively. Probiotic tolerance at low pH and the presence of bile salts of Lactiplantibacillus plantarum D4 consistently showed a high survival rate in medium B compared to MRS. Based on these results, the components and proportions used in medium B were suitable for the growth of L. plantarum D4 as a halal probiotic starter candidate.